iRGD-Targeted Biosynthetic Nanobubbles for Ultrasound Molecular Imaging of Osteosarcoma - Liu T; Liang X; Liu W; Yang S; Cui T; Yan F; Li Z (International Journal of Nanomedicine)
Tingting Liu,1– 3 Xiaoxin Liang,4 Wei Liu,5 Shuai Yang,6 Tao Cui,7 Fei Yan,3 Zhenzhou Li1,2 1Department of Ultrasound, The second People’s Hospital of Shenzhen, The First Affiliated Hospital of Shenzhen University, Shenzhen, 518061, People’s Republic of China; 2Graduate School, Guangxi University of Chinese Medicine, Nanning, 530200, People’s Republic of China; 3CAS Key Laboratory of Quantitative Engineering Biology, Shenzhen Institute of Synthetic Biology, Shenzhen Institutes of Advanced Technology, Chinese Academy of Sciences, Shenzhen, 518055, People’s Republic of China; 4Department of Ultrasound, Sun Yat-Sen University Cancer Center, Guangzhou, 510060, People’s Republic of China; 5School of Life Sciences, Sun Yat-Sen University, Guangzhou, 510275, People’s Republic of China; 6Department of Clinical and Research, Shenzhen Mindray Bio-Medical Electronics Co, Ltd, Shenzhen, 518055, People’s Republic of China; 7Medical Imaging center, Shenzhen Yunshan Yunli Hospital, Shenzhen, 518055, People’s Republic of ChinaCorrespondence: Fei Yan; Zhenzhou Li, Email fei.yan@siat.ac.cn; lizhenzhou2004@126.comPurpose: Osteosarcoma is the most common primary malignant tumor of the bone. However, there is a lack of effective means for early diagnosis due to the heterogeneity of tumors and the complexity of tumor microenvironment. αvβ 3 integrin, a crucial role in the growth and spread of tumors, is not only an effective biomarker for cancer angiogenesis, but also highly expressed in many tumor cells. Here, we selected it as the imaging target and fabricated iRGD-sGVs acoustic probe for the early-stage diagnosis of osteosarcoma.Materials and Methods: Biological nanoscale gas vesicles (sGVs) were extracted from Serratia 39006. Their morphology was analyzed with phase contrast and transmission electron microscopes. Particle size and zeta potential were measured by a Zetasizer. iRGD-targeted molecular probes (iRGD-sGVs) were prepared by coupling iRGD to sGVs via Mal-PEG2000-NHS. Targeting efficiency of iRGD-sGVs was evaluated using flow cytometry and confocal microscopy on endothelial and K7M2 osteosarcoma cells. In vivo contrast-enhanced ultrasound imaging of iRGD-sGVs was performed in osteosarcoma-bearing mice, and the expression of avβ3 in osteosarcoma was detected through immunofluorescence staining assay. Biocompatibility of sGVs was assessed by hemolysis tests, CCK8 cytotoxicity assays, blood biochemical tests, and HE staining.Results: sGVs from Serratia .39006 have smaller particle size (about 160 nm). Our in vitro and in vivo experiments showed the specifically binding ability of iRGD-sGVs to both vascular endothelial cells and tumor cells, producing the stronger and longer acoustic signals in tumors in comparison with the control probe. Immunofluorescence staining results indicated iRGD-sGVs were co-localized with highly expressed αvβ 3 in tumor vasculature and osteosarcoma cells. Biocompatibility analysis showed no significant cytotoxicity of iRGD-sGVs to mice.Conclusion: Our study provides a new strategy for early diagnosis of osteosarcoma. Keywords: ultrasound molecular imaging, ultrasound contrast agents, gas vesicles, internalizing RGD, tumor imaging